2020
DOI: 10.3390/w12061752
|View full text |Cite
|
Sign up to set email alerts
|

Improving Inter-Laboratory Reproducibility in Measurement of Biochemical Methane Potential (BMP)

Abstract: Biochemical methane potential (BMP) tests used to determine the ultimate methane yield of organic substrates are not sufficiently standardized to ensure reproducibility among laboratories. In this contribution, a standardized BMP protocol was tested in a large inter-laboratory project, and results were used to quantify sources of variability and to refine validation criteria designed to improve BMP reproducibility. Three sets of BMP tests were carried out by more than thirty laboratories from fourteen countrie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

7
63
2
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 54 publications
(73 citation statements)
references
References 53 publications
(121 reference statements)
7
63
2
1
Order By: Relevance
“…Various explanations for the observed differences have been proposed, including measurement errors and differences among inocula, as recently reviewed [6,[10][11][12]. A recent large interlaboratory study found evidence that differences among measurement methods are important [6]. Therefore, learning more about differences between measurement methods could lead to improvements in BMP standardization, and this was the focus of the current paper.…”
Section: Introductionmentioning
confidence: 90%
See 4 more Smart Citations
“…Various explanations for the observed differences have been proposed, including measurement errors and differences among inocula, as recently reviewed [6,[10][11][12]. A recent large interlaboratory study found evidence that differences among measurement methods are important [6]. Therefore, learning more about differences between measurement methods could lead to improvements in BMP standardization, and this was the focus of the current paper.…”
Section: Introductionmentioning
confidence: 90%
“…Even though some guidelines were published since 2006 [3,5,6] and different interlaboratory tests have been performed, there is no standard method for BMP measurement [7]. Variability in BMP measured by different methods in different laboratories is a significant problem, as shown by round robin tests [6,8,9].…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations